Musik Kompang dalam Penciptaan Komposisi Musik “Kompangku” - Hamzaini Hamzaini; Yesriva Nursyam; Aan Nursyam; Ricky Warman Putra; Jhori Andela (SENDRATASIK UNP, 2022)
The musical of composition "Kompangku" is a musical work inspired by Kompang's percussion music that grew and developed in Rengat, Indragiri Hulu. As far as studies have been conducted on Kompang’s music, the authors can state that in space and time the up-beat on the peningkah has a very important role in producing interlocking rhythms that accumulate in the rhythmic time cycle cycle, so that producing a formula for ostinato-moving rhythms. The principle of Kompang's rhythmic playing of music patterns which produces an up-beat 'space and time' fabric, of course, it cannot be denied that the fabric is the result of the game of various peningkah and basic variations. In this case, the space and time in question are "space" created by time leading up to and after the up-beat accompanied by "rhythmic time" where the rhythmic playing takes place. This is the focus of working on a musical composition entitled "Kompangku" which is sourced from Kompang's music.